1989
DOI: 10.1038/bjc.1989.211
|View full text |Cite
|
Sign up to set email alerts
|

Activation of protein kinase C induces differentiation in the human T-lymphoblastic cell line MOLT-3

Abstract: S_uany We attempted to determine whether or not activation of calcium phospholipid-dependent protein kinase C (PKC) is associated with the induction of differentiation by 12-O-tetradecanoylphorbol-13-acetate (TPA) in the human T-lymphoblastic cell line MOLT-3. PKC activities were assayed in MOLT-3 and its five subclones resistant to TPA-induced cell differentiation. The cytosolic PKC activities of TPA-resistant subclones were 36-53% of that of the parental MOLT-3 cells. TPA treatment led to a rapid decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…TPA is a well known, potent inducer of di erentiation in cells such as myeloid leukemia cells and neuroblastoma (Rovera et al, 1979(Rovera et al, , 1982Bouche et al, 1995;Heikkila et al, 1989;Yamauchi et al, 1989). We previously showed that the androgen-independent human prostate cancer cell line TSU-Pr1 di erentiates into microglia-like cells upon treatment with TPA (Itayasu et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…TPA is a well known, potent inducer of di erentiation in cells such as myeloid leukemia cells and neuroblastoma (Rovera et al, 1979(Rovera et al, , 1982Bouche et al, 1995;Heikkila et al, 1989;Yamauchi et al, 1989). We previously showed that the androgen-independent human prostate cancer cell line TSU-Pr1 di erentiates into microglia-like cells upon treatment with TPA (Itayasu et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…3T3 mouse fibroblasts (12) and resting T lymphocytes (13) and 2) inhibition of cell proliferation and stimulation of differentiation. The latter effect was first demonstrated when the HL60 promyelocytic leukemia cell line was induced to differentiate into a macrophage like phenotype (14) and subsequently the same phenomenon was observed in other cell types (15). Protein kinase C participates in a complex network of signal transduction pathways involving both tyrosine kinase receptors and G protein coupled receptors.…”
Section: Introductionmentioning
confidence: 82%
“…stimulation of quiescent cells into growth and subsequent mitosis or inhibition of cell proliferation and stimulation of terminal differentiation. 16,17 It was worthy to mention that TPA could be found in many Chinese medicinal herbs and food-types which suggested that the diet of Chinese individual might make them more vulnerable to NPC. 4,5,18,19 So the original intention of our present study was to use proteomics technology to seek some key proteins which could help to clarify the mechanism of TPA promoting NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies showed that a number of cultured cell lines were responsive to TPA to fall into two categories, viz. stimulation of quiescent cells into growth and subsequent mitosis or inhibition of cell proliferation and stimulation of terminal differentiation. , …”
Section: Discussionmentioning
confidence: 99%